State Regulation of Training for United Territorial Communities By Higher Educational Institutions of Ukraine - Zastrozhnokova, Iryna (Pressing Problems of Public Administration, 2019)
The article analyzes the state and aspects of state regulation of training of higher educational institutions, outlines the main problems and perspective directions of state regulation of the activities of higher educational institutions. The main missions and powers of the Ministry of Education and Science of Ukraine in regulation of the activity of higher educational institutions are considered. It indicates a signi cant discrepancy between the needs of the society in the personnel and the offer of graduates of certain professions, as well as the serious need of united territorial communities, in particular rural, in some skilled personnel, including teachers, doctors and agricultural workers. The law of Ukraine, which regulates the priority of enrollment of budget places in higher educational establishments of those entrants who wish to work in the countryside, is analyzed. Higher education should provide the perspective and current educational needs of people, society and national economy. The main task of state regulation in the market of educational services is to create the necessary conditions for the activities of higher educational institutions that provide educational services. One of the main problems of the state regulation of the educational services market is the discrepancy of the educational and educational process in educational institutions with the needs of the development of the national economy. Many rural communities experience a severe shortage of skilled teachers, doctors and agricultural workers. In order to overcome this de cit in early 2019, a law was passed in Ukraine that states that applicants who wish to work in rural areas will be able to take advantage of the right of  rst-time admission to the budget for the  rst time. In our opinion, this is a very important step for improving the living standards of rural communities. We believe that in order to further support the village infrastructure and prevent the mass exodus of youth from rural communities, it is necessary to introduce similar programs for other universities, in particular for agrarian, which train specialists for agriculture.